Biotechnology applied to fish reproduction: tools for conservation - de Siqueira-Silva, Diógenes Henrique; Saito, Taiju; Dos Santos-Silva, Amanda Pereira [UNESP]; da Silva Costa, Raphael [UNESP]; Psenicka, Martin; Yasui, George Shigueki (Springer Nature, 2018)
This review discusses the new biotechnological tools that are arising and promising for conservation and enhancement of fish production, mainly regarding the endangered and the most economically important species. Two main techniques, in particular, are available to avoid extinction of endangered fish species and to improve the production of commercial species. Germ cell transplantation technology includes a number of approaches that have been studied, such as the transplantation of embryo-to-embryo blastomere, embryo-to-embryo differentiated PGC, larvae to larvae and embryo differentiated PGC, transplantation of spermatogonia from adult to larvae or between adults, and oogonia transplantation. However, the success of germ cell transplantation relies on the prior sterilization of fish, which can be performed at different stages of fish species development by means of several protocols that have been tested in order to achieve the best approach to produce a sterile fish. Among them, fish hybridization and triploidization, germline gene knockdown, hyperthermia, and chemical treatment deserve attention based on important results achieved thus far. This review currently used technologies and knowledge about surrogate technology and fish sterilization, discussing the stronger and the weaker points of each approach.
Keywords: Chimera; Fish sterilization; Germ cell transplantation; Surrogate broodstock technology